Microplastics do not affect standard ecotoxicological endpoints in marine unicellular organisms. (June 2019) - Gambardella, Chiara; Piazza, Veronica; Albentosa, Marina; Bebianno, Maria João; Cardoso, Cátia; Faimali, Marco; Garaventa, Francesca; Garrido, Soledad; González, Sergio; Pérez, Sara; Sendra, Marta; Beiras, Ricardo
Abstract: In this study, the acute toxicity of microplastics (MPs) on unicellular organisms as marine decomposers and microalgae was assessed, by evaluating standards endpoints included in International Standard Organization (ISO) protocols. The bacteria Vibrio fischeri and the diatom Phaeodactylum tricornutum were exposed to different sizes (1–500 μm) of polyethylene MPs in order to evaluate bioluminescence inhibition and microalgal growth. No acute toxicity was found on bacteria or microalgae in an order of magnitude above environmentally relevant concentrations, suggesting that tested MPs did not affect the investigated biological processes. In conclusion, standard ecotoxicological endpoints are not sufficiently sensitive to assess the potential effects of MPs on decomposers and primary producers, conversely to nanoplastics. These findings highlight that the current approach for MP risk assessment in unicellular species should be revised, by providing alternative endpoints to be included in standardized protocols, able to monitor the fate and biological effects of MPs. Graphical abstract: Unlabelled Image Highlights: Acute toxicity of polyethylene MPs on marine bacteria and microalgae was assessed. Different sizes (1–500 μm) of MPs at low and high concentrations were tested. MPs did not affect bacteria and algal growth inhibition. Standard endpoints are not sufficiently sensitive to assess MP toxicity. Alternative endpoints should be investigated and included in standardized protocols.